ANALYSIS AND SYNTHESIS OF DISSIMILAR GEOSPATIAL DATA (CONSTRUCTION OF METAMODELS FOR GEOLOGICAL INFORMATION) - Zakchariy, N.; Polinovskyi, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Analyzed the specific geological information. Suggested the method of finding hidden regularities and way of integrating diverse geodata into a single, homogeneous environment. Various methodological approaches to processing of geological information leading to multivariate, controversial, subjective opinion and, according to the authors, requires the development of standardized methods processing of geological information and standardization (create geometadata).